Social affiliation networks: Identification of key agents and actors in the management of technological innovation in SMEs. - Mateo-Mejía, C.; Armas-Arévalos, E.; Bautista-Hernández, M.A. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
The objective of this research was to identify the degree of linkages between small and medium-sized manufacturing enterprises (SMEs) and the main agents managing technological innovation within a network in the Cuitzeo region of the state of Michoacán, Mexico. To identify these elements, the methodology known as Social Network Analysis (SNA), an analysis based on graph theory, developed by Leonhard Euler, was used. To map the identification of key actors in IT management, some indicators were employed to analyze the general structure of the network, including density, transitivity, degree of centralization, relationships and the strength of the links generated in the network. A non-experimental cross-sectional research design was employed, using the database of the National Institute of Statistics and Geography (INEGI) via the National Statistical Directory of Economic Units (DENUE). Field information was collected from a sample of 161 small and medium-sized enterprises (SMEs) in the manufacturing sector. The size of the affiliation network consisted of eight nodes and 12 links between agents and actors within the general structure of the network. The analysis revealed that manufacturing SMEs exhibited a stronger relationship with suppliers (27.35%), compared to the less marked relationship they established with other companies in the same sector (1.41%). It is also noteworthy that 43 companies (26.70%) did not establish any links or ties with other actors and agents during the first half of 2022. It was concluded that there are few links with other actors in the management of technological innovation within the SMEs under study. Furthermore, there are no close links between them, as they presented a poor administrative and productive organization in which the technological component was not clearly appreciated. The most common collaboration agreements with external agents were seminars and training courses (34.8%), while the least demanded linkage was internal training (2.5%).